IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SEBAGAI PENGUATAN CIVIC CULTURE DI MAN 2 MODEL MATARAM - Rispawati; Basariah; Zubair; Wiwi Adejuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to determine the implementation of P5 as a strengthening of Civic Culture and the supporting and inhibiting factors for the implementation of P5 activities as a strengthening of Civic Culture at MAN 2 Model Mataram. This research uses a qualitative approach with a case study type of research. Informants in this study were determined by purposive sampling technique. To collect data using observation, interview, and documentation techniques. The data that has been collected is then analyzed using the Miles and Huberman method with data reduction, data presentation, and conclusion drawing stages. To test the validity of the data using three types of triangulation, namely source, time, and method. The results of this study indicate that, the form of implementation of the Pancasila student profile strengthening project (P5) as a strengthening of Civic Culture at MAN 2 Mataram Model is: 1). Visiting cultural sites, 2) Oral literature, 3) Traditional food, 4) Traditional games, 5) Regional songs, 6) Folklore, 7) Traditional musical instruments, 8) Traditional clothing, 9) Customary law, 10) Religious moderation, 11) Sasak traditional dance, and 12) Sasak traditional wedding procession. Supporting factors for the implementation of P5 activities include the competence of teachers as P5 implementers, support and cooperation of teachers/staff/community, availability of a place to implement P5 activities, availability of implementation facilities, participation and enthusiasm of students and the availability of implementation guidelines and P5 teaching modules. Meanwhile, the inhibiting factor in the implementation of activities is the lack of support from parents in the implementation of P5.